2021
DOI: 10.3390/catal11010102
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of Urea in Alkaline Solution Using Nickel Hydroxide Activated Carbon Paper Electrodeposited from DMSO Solution

Abstract: Electrooxidation of urea plays a substantial role in the elimination of urea-containing wastewater and industrial urea. Here, we report the electrodeposition of nickel hydroxide catalyst on commercial carbon paper (CP) electrodes from dimethyl sulphoxide solvent (Ni(OH)2-DMSO/CP) for urea electrooxidation under alkaline conditions. The physicochemical features of Ni(OH)2-DMSO/CP catalysts using scanning electron microscopy and X-ray photoelectron spectroscopy revealed that the Ni(OH)2-DMSO/CP catalyst shows na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…In addition, it is worth noting that the intensity of the sodium peak on the surface of inorganic acid spray-dried products is approximately twice that of organic acid spray-dried products, which indicates that the inorganic anion can react with the sodium cation to increase sodium ion pollution. In Figure i–l, the results of O 1s analysis show that only inorganic acid spray-dried products show crystalline oxygen, while organic acid spray-dried products are mainly composed of 531.2–531.9 eV organic oxygen and 532.6 eV chemical oxygen, which mainly come from carboxyl and hydroxyl groups. Therefore, overactive sodium cations are easily combined with the oxygen in the anion of leaching agents, which will further adsorb or react to generate more organic oxygen, chemical oxygen, or free oxygen, forming more surface pollutants. The best solution is to choose NH 3 ·H 2 O instead of NaOH to avoid the introduction of sodium ions in the pH adjustment step.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is worth noting that the intensity of the sodium peak on the surface of inorganic acid spray-dried products is approximately twice that of organic acid spray-dried products, which indicates that the inorganic anion can react with the sodium cation to increase sodium ion pollution. In Figure i–l, the results of O 1s analysis show that only inorganic acid spray-dried products show crystalline oxygen, while organic acid spray-dried products are mainly composed of 531.2–531.9 eV organic oxygen and 532.6 eV chemical oxygen, which mainly come from carboxyl and hydroxyl groups. Therefore, overactive sodium cations are easily combined with the oxygen in the anion of leaching agents, which will further adsorb or react to generate more organic oxygen, chemical oxygen, or free oxygen, forming more surface pollutants. The best solution is to choose NH 3 ·H 2 O instead of NaOH to avoid the introduction of sodium ions in the pH adjustment step.…”
Section: Resultsmentioning
confidence: 99%
“…Ni and Ni-based hybrid electrodes are widely employed as electrocatalysts in the oxidation and determination of organics such as methanol, ethanol, glucose, cyclohexanol, and aspirin. Aladeemy et al 10 successfully demonstrated the electrolysis of urea to produce H 2 using Ni electrodes in an alkaline medium. Several recent experiments and theoretical investigations have been conducted to uncover urea hydrolysis in the presence of urease (containing Ni active sites).…”
Section: Introductionmentioning
confidence: 99%
“…NiOOH is a highly active catalyst for UOR, with a low overpotential and high current density. However, NiOOH is also susceptible to deactivation, so researchers are exploring strategies to improve its stability and durability 11 . Glassy carbon electrodes modified with electropolymerized polyaniline (PANI) functionalized by the electrodeposition of CuO x and NiO x nanoparticles (NPs) are suggested as effective and stable electrocatalysts toward urea oxidation reaction (UOR) 12 .…”
Section: Introductionmentioning
confidence: 99%